The influence of shahwah on the behavior of man: a comparative study of the Qur’anic and the neo-classical secular concepts - Amafua, Mahfuth Khamis (2015)

(untitled)
The neo-classical secularist school sees man as an economic material object whose sole objective is to maximize his unlimited worldly Shahwah. He has no control over his Shahwah. His value is measured by his ability to convert that Shahwah into material unlimited wants. He has no naÎÊb in Ókhirah. On the other hand, the Qur’Én looks at Shahwah from the positive and negative perspectives. It provides man with means to overcome this Shahwah and to convert negative Shahwah to a positive one. There is a dearth of extant literature that has extensively and comparatively investigated the extent to which al-Shahwah influences human behavior. The present study adopts content analysis to critically analyze the concept of Shahwah from the neo-classical secular view and the Qur’Énic perspective. The findings provide insights into how the secular approach is individualistic and destructive as opposed to the Qur’Énic treatment which is educative, transformatory and constructive.